PENGARUH METODE THINKING ALOUD PAIR PROBLEM SOLVING TERHADAP PENINGKATAN KEMAMPUAN MENYELESAIKAN MASALAH MATEMATIKA MAHASISWA - Yuntawati, Yuntawati; Moh. Supratman, Moh. (Media Pendidikan Matematika, 2019)
The purpose of this study was to determine the effect of the Thingking Aloud Pair Problem Solving (TAPPS) Method on the Mathematical Problem Solving Capabilities of Semester 1 Students in Mathematics Education Program FPMIPA IKIP Mataram on Calculus I Subjects. The research method used was a quasi single subject experiment with group design (group design). In this study comparisons between groups using the average score (mean) with AB design, namely measurement of target behavior in the baseline phase (A) before the application of the TAPPS method carried out in two sessions and the provision of intervention (B) or the application of the TAPPS method performed in two sessions anyway. The instrument used was a lecturer and student activity observation sheet, to collect data about developments in each session or stage, a student interview guide, used to dig deeper information about the application of the TAPPS learning method, and a problem solving ability test sheet. The results of this study indicate an increase in the average value of session 1 by 60.17 and session 2 by 60.67 in the baseline phase (A) to session 3 by 66.83 and session 4 by 71.5 in the intervention phase (B). Based on the results of the study it can be concluded that the application of the TAPPS method has a positive effect on the ability to solve calculus I problems.